Low temperature methanation of CO2 over an amorphous cobalt-based catalyst. Issue 11 (2nd February 2021) - Tu, Jinghui; Wu, Haihong; Qian, Qingli; Han, Shitao; Chu, Mengen; Jia, Shuaiqiang; Feng, Ruting; Zhai, Jianxin; He, Mingyuan; Han, Buxing
Abstract : It is discovered that an amorphous transition metal catalyst Co–Zr0.1–B–O could effectively accelerate CO2 methanation, at a rate that is comparable to or even higher than that of some noble metal catalysts under similar conditions. Abstract : CO2 methanation is an important reaction in CO2 valorization. Because of the high kinetic barriers, the reaction usually needs to proceed at higher temperature (>300 °C). High-efficiency CO2 methanation at low temperature (<200 °C) is an interesting topic, and only several noble metal catalysts were reported to achieve this goal. Currently, design of cheap metal catalysts that can effectively accelerate this reaction at low temperature is still a challenge. In this work, we found that the amorphous Co–Zr0.1 –B–O catalyst could catalyze the reaction at above 140 °C. The activity of the catalyst at 180 °C reached 10.7 mmolCO2 gcat −1 h −1, which is comparable to or even higher than that of some noble metal catalysts under similar conditions. The Zr promoter in this work had the highest promoting factor to date among the catalysts for CO2 methanation. As far as we know, this is the first report of an amorphous transition metal catalyst that could effectively accelerate CO2 methanation. The outstanding performance of the catalyst could be ascribed to two aspects. The amorphous nature of the catalyst offered abundant surface defects and intrinsic active sites. On the other hand, the Zr promoter could enlarge the surface area of the catalyst, enrich the Co atoms on the catalyst surface, and tune the valence state of the atoms at the catalyst surface. The reaction mechanism was proposed based on the control experiments.